2011
DOI: 10.1007/s13197-011-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of groundnut oil during continuous and intermittent frying

Abstract: The quality of refined groundnut oil, as affected by frying Poori, was assessed with respect to two types of frying operations viz., continuous frying and intermittent frying. Continuous frying was carried out consistently for 8 h, whereas intermittent frying was performed for 2 h everyday for 4 days for a total of 8 frying hours. The purpose of the study was to compare the level of deterioration that occurred during the two operations. Among the parameters studied, peroxide value (11.3±0.26 meqO 2 /kg), anisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Polycotton fabric pieces were stained with peanut oil. Peanut oil is usually preferred for deep frying because it is relatively stable with a high smoke point (Das et al 2013 ). This explains the rationale behind the use of peanut oil in the present study to obtain tough stains on the fabric pieces.…”
Section: Resultsmentioning
confidence: 99%
“…Polycotton fabric pieces were stained with peanut oil. Peanut oil is usually preferred for deep frying because it is relatively stable with a high smoke point (Das et al 2013 ). This explains the rationale behind the use of peanut oil in the present study to obtain tough stains on the fabric pieces.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they reported that the intermittent heating would result in more damage to the oil compared with the continuous heating. It is believed that the decomposition and formation of carbonyl and hydroperoxides during the frequent heating and cooling (due to increase of oxygen solubility in the oil) periods, respectively, lead to higher oil degradation [73,76]. More instances are presented in the Table 3.…”
Section: Operation Conditionsmentioning
confidence: 99%
“…The stability of frying oil is a crucial factor in the quality and health effect of both fried foods and oils [5]. Therefore, it is imperative to assess oil quality to avoid the use of deteriorated oil [5] by the best methods recommended for evaluating frying degradation, which are the determination of polar compounds [6] and the determination of polymers [7]. Besides, essays on deep-fat frying in a standard fryer remain the best method to test frying performance of oils [8].…”
Section: Introductionmentioning
confidence: 99%